Recalcitrant nitrogen pool dynamics in forest and grassland soils - Kaye, Jason Philip, author; Binkley, Dan, advisor; Ryan, Michael R., committee member; Kelly, Eugene F., committee member; Burke, Ingrid C., committee member (Colorado State University. Libraries, 2000)
Most nitrogen (N) cycling research has focused on the relatively small pool of labile N that is cycled annually by plants and soil microorganisms. However, most ecosystem N is in soil organic pools that are not actively cycled by plants and microbes. The purpose of this dissertation was to measure the pool size, accumulation rate, and N sink potential of soil organic N pools that were not readily available to microorganisms (called non-labile or recalcitrant). I used soils from: 1) a subtropical plantation with three tree species and a 6 to 9 year-old 15N addition, 2) a Taiga floodplain successional sequence with 1 to 500 + year-old terraces and an 15N label added in the laboratory, and 3) a Great Plains soil C and texture gradient with a 2 year-old I5N addition. I separated total soil N and 15N into labile and non-labile pools using long-term incubations with repeated leaching. In the tropical plantation, tree species did not affect non-labile N pools and 77 and 65 % of total soil N and 15N were not labile, respectively. During Taiga floodplain succession, non-labile N pools increased by 2 g N/m2/yr for the first 50 years and then by 0.6 g N/m2/yr for the next 200 years. Thirty percent of the 15N added 3 weeks prior to the incubation was non-labile. In grassland soils, 80 and 50 % of total soil N and 15N were not labile, respectively. Soil C (r2 = 0.72) correlated better with N pool sizes than soil texture (r2 = 0.27). Across all three sites, non-labile N correlated with non-labile C (r2 = 0.68) and labile N correlated with labile C (r2 = 0.74). Non-labile N pools increase in size rapidly and release N slowly. They will be an immediate, large, and long-term sink for N added to soils. Rapid sequestration of N into a slow-release pool may explain the asynchrony between N inputs and outputs in terrestrial ecosystems. Incorporation of N into non-labile pools may or may not require microbial immobilization and abiotic mechanisms of N retention warrant further study.
Keywords: ecology; soil sciences; forestry; range management